Analysis of workers' perception and demographic factors: An insight into the Slovenian gig economy - Matevž Antloga; Ivona Huek (Naše gospodarstvo / Our Economy, 2024)
This study examines the gig economy in Slovenia, with a particular emphasis on the perceived benefits and challenges for gig workers within this emerging labour model. The research aims to capture the implications of flexible, project-based employment in a smaller European context, as this trend becomes increasingly prevalent globally. A quantitative approach was employed to survey 34 gig workers in Slovenia. The survey analysed their demographic characteristics, reasons for engaging in gig work, and the benefits and challenges they experience. In the findings, 64% of respondents specifically identified schedule flexibility as a predominant benefit of gig work. However, it also uncovers substantial challenges, including increased market competition and a lack of social benefits. Moreover, the research suggests that perceptions of the gig work benefits are widely acknowledged across various age groups and educational levels, with no significant variation. Nevertheless, the findings indicate a gender disparity in gig work perceptions, with males perceiving higher levels of financial freedom and professional development than women. This research suggests the need for policies aimed at ensuring equity and further research into harmonizing gig work with supportive labour market policies.
Keywords: J26; L26; M54; 330; Gig economy; Flexibility; Professional development; Social benefits; Demographic disparities